When God Speaks through Change: Preaching in Times of Congregational Transition - Satterlee, Craig A. (Rowman & Littlefield Publishers, 2005)
At times, a congregational transition looms so large in a sermon that it becomes the lens through which scripture is interpreted, the congregation is addressed, the preacher is heard, and God is experienced. Homiletics professor and parish pastor Craig Satterlee reflects in this accessible, provocative volume about on how to integrate such significant events in a congregation’s life into the preaching ministry of the church. Rather than offering a blueprint for preaching, however, he walks along pastors, seminarians, and other congregational leaders who want to make sure the Gospel, not an agenda, is preached.